Foot Care in Preventing Diabetic Ulcers in Diabetes Mellitus Patients at Tanah Tinggi Health Center - Faswita, Wirda; Herawati, Leli (Talenta Publisher, 2022)
Foot care is an action that aims to prevent diabetic ulcers including washing and drying the feet, checking the condition of the feet every day, taking care of nails, being careful when exercising, and protecting the feet with shoes and socks (Ariyanti, 2012). This action is carried out on the elderly who suffer from Diabetes Mellitus and have the potential to experience health problems. The purpose of this activity is to carry out early detection and prevent the occurrence of Diabetic Ulcers. The activity was carried out on June 17, 2021, UPTD Tanah Tinggi Public Health Center, Binjai City. The implementation of these activities gives positive results for the elderly. People who check themselves can find out the condition of their feet and add information in the prevention of diabetic ulcers with the result that participants enthusiastically ask about foot care and are able to explain how to prevent diabetic ulcers.